Upper extremity function and disability recovery with vibration therapy after stroke: a systematic review and meta-analysis of RCTs - Lu, Yueh-Hsun; Chen, Hung-Ju; Liao, Chun-De; Chen, Po-Jung; Wang, Xin-Miao; Yu, Chieh-Hsiang; Chen, Po-Yin; Lin, Chueh-Ho (Journal of neuroengineering and rehabilitation, 2024)
This study aimed to investigate the therapeutic effects of vibration therapy for improving upper extremity motor impairment, function, and disability recovery in people with stroke. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. PubMed, EMBASE, the Cochrane Library Database, Physiotherapy Evidence Database (PEDro), China Knowledge Resource Integrated Database, and Google Scholar were searched from inception to May 31, 2024. Randomized controlled trials (RCTs) that evaluated the effects of vibration therapy on upper extremity motor impairment, function, and disability recovery post-stroke were analyzed. Participants with a diagnosis of stroke with hemiplegia (or hemiparesis) were recruited. Methodological quality assessment was performed using the PEDro quality score. Upper extremity motor impairment, function, and disability were the primary outcomes. Upper extremity motor impairment was measured using the Fugl-Meyer Assessment scale and other methods. Upper extremity functions were evaluated using the Wolf Motor Function test or other tools assessing manipulative activities. Disability was assessed using the Functional Independence Measure, Barthel index, and other methods. Overall, 30 RCTs including 1621 people with stroke were selected. Compared with the control, vibration therapy exerted significant effects on upper extremity motor impairment [standardized mean difference (SMD) = 1.19; p < 0.00001)], function (SMD = 0.62; p < 0.00001), and disability recovery (SMD = 1.01; p < 0.00001). The subgroup analysis revealed that focal vibration therapy (SMD = 2.14) had favorable effects on disability recovery compared with whole-body vibration therapy (SMD = 2.0). Interventions lasting 4-8 weeks showed significant improvements in motor impairment (SMD = 1.19), motor function (SMD = 0.57), and disability (SMD = 0.84); additionally, the effects of vibration therapy combined with conventional rehabilitation (SMD = 1.03) were superior to those of vibration therapy alone (SMD = 0.21). Vibration therapy may be a reliable rehabilitation program to improve upper extremity motor functions and disabilities. Furthermore, vibration therapy should be performed at the earliest possibility after stroke for at least 4-8 weeks. Trial registration The protocol of this study was registered with PROSPERO (Registration number: CRD42022301119).